1 The Public Records of the Colony of Connecticut 15 (J. Hammond Trumbull ed., 1850) (enacted 1637) - (:unkn) unknown (My University, 1637)
It is ordered that all prsons shall beare Armes that are aboue the age of sixteene yeeresm except they doe tender a sufficient excuse [to] the Corte & the Cort allowe the same
Keywords: REQUIRED POSSESSION